Program Edukasi Heritage Tourism Berbasis Kearifan Lokal untuk Meningkatkan Kesadaran Pelestarian Sejarah pada Mahasiswa Pariwisata UNIKA Medan - Furqan Furqan (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2026)
Through a local knowledge based cultural heritage tourism education program, this community service activity aims to improve the understanding of tourism students at the Catholic University of Santo Thomas Medan about local history and cultural preservation. The community service activity was carried out at the Tjong A Fie historical and cultural tourism site in Medan City in March 2026. Through engaging discussions, historical educational tours, explanations of cultural heritage sites, and observation activities, the implementation strategy used an educational, participatory, and experiential learning approach. The concepts of historical tourism, community-based tourism, the value of cultural acculturation, and the importance of cultural heritage preservation in promoting sustainable tourism were among the topics discussed in the content. Students' understanding of local historical and cultural values ​​​​and their knowledge of the importance of preserving regional cultural identity increased as a consequence of this activity. Students also gained direct experience in understanding cultural heritage tourism and the importance of community involvement in the management of historical tourist sites. It is hoped that this program will become an example of cultural heritage-based tourism education that encourages the growth of sustainable cultural tourism in North Sumatra and Medan City.